The base of the Norwegian-British-Swedish Antarctic Expedition, 1949–52 - Reece, Alan (Polar Record, 1953)
It was originally planned that the base, which was situated in Dronning Maud Land in lat. 71° 6' S., long. 10° 58' W., should consist of three large and one small huts: Large hut 1. Accommodation for eight men, radio office, dark room and sick-bay. Large hut 2. Accommodation for six men, kitchen and mess. Large hut 3. Workshop, meteorological office and laboratories. Small hut. Two Diesel generators.